2010
DOI: 10.2500/ajra.2010.24.3475
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics in Endoscopic Sinus Surgery: A Short Follow-Up Study

Abstract: The use of an antibiotic (amoxicillin/clavulanate) in the postoperative period is able to improve the outcome in the early blood crust healing phase: nasal obstruction and drainage are reduced and the endoscopic score objectively showed a faster recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 14 publications
1
66
1
1
Order By: Relevance
“…2008). The use of an antibiotic (amoxicillin/clavulanate) in the postoperative period is able to improve the outcome in the early blood crust healing phase: nasal obstruction and drainage are reduced and the endoscopic score objectively showed a faster recovery (Albu S. 2010). Patients recover in 9 to 10 days after ESS when provided with appropriate pain management.…”
Section: Principles Of Management In Different Stages After Operationmentioning
confidence: 99%
“…2008). The use of an antibiotic (amoxicillin/clavulanate) in the postoperative period is able to improve the outcome in the early blood crust healing phase: nasal obstruction and drainage are reduced and the endoscopic score objectively showed a faster recovery (Albu S. 2010). Patients recover in 9 to 10 days after ESS when provided with appropriate pain management.…”
Section: Principles Of Management In Different Stages After Operationmentioning
confidence: 99%
“…The result was not significant for the subgroup of studies involving amoxicillin alone. The NNH for candidiasis was 27 (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In addition to explicit candidiasis, one trial reported rates of diaper rash of about 50% among infants treated with amoxicillin-clavulanic acid.…”
Section: /1688mentioning
confidence: 99%
“…Three years later, Liang et al [17] showed that there was no difference amongst patients treated with Chinese herbal medicine, amoxicillin, or placebo in the postoperative period in the Chinese version of the Rhinosinusitis Outcome Measure (CRSOM-31) and endoscopic scores. On the contrary, in 2010, Albu and Lucaciu [18] were able to show improved endoscopic scores on postoperative day number 5 and 12 with postoperative antibiotic treatment.…”
Section: Evidence Regarding Postoperative Antibioticsmentioning
confidence: 82%